2006
DOI: 10.1002/ijc.22313
|View full text |Cite
|
Sign up to set email alerts
|

Life‐style and environmental factors in the development of nasal NK/T‐cell lymphoma: A case–control study in East Asia

Abstract: Cases of nasal NK/T-cell lymphoma (NKTCL) occur occasionally in Asian and Latin American countries but rarely in Western countries. The etiological role of life-style and environmental factors in nasal NKTCL was investigated. Five university hospitals in Japan and one each in Korea and China participated in this study; a total of 88 cases and 305 hospital controls were accrued during 2000-2005. The odds ratio (OR) of NKTCL obtained after adjustments of age, sex and country was 4.15 (95% confidence interval (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 26 publications
(24 reference statements)
1
29
0
Order By: Relevance
“…Furthermore, this subtype was the most common T-cell NHL in Guatemala (7.8%), with high frequencies also observed in Chile (2.6%) and Peru (2.9%). An increased frequency of ENKTL also has been reported in Hong Kong and other Asian countries, [7][8][9][10][11][43][44][45] and studies have demonstrated a strong association between this lymphoma and Epstein-Barr virus infection. 1,7,8,13,44 Furthermore, Morton et al have reported a greater incidence of ENKTL among Asian Americans, 3 and other epidemiologic studies have demonstrated little difference in the incidence of this subtype among foreign-born and US-born Asians, supporting the role of host susceptibility in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this subtype was the most common T-cell NHL in Guatemala (7.8%), with high frequencies also observed in Chile (2.6%) and Peru (2.9%). An increased frequency of ENKTL also has been reported in Hong Kong and other Asian countries, [7][8][9][10][11][43][44][45] and studies have demonstrated a strong association between this lymphoma and Epstein-Barr virus infection. 1,7,8,13,44 Furthermore, Morton et al have reported a greater incidence of ENKTL among Asian Americans, 3 and other epidemiologic studies have demonstrated little difference in the incidence of this subtype among foreign-born and US-born Asians, supporting the role of host susceptibility in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…ENKTL is a rare disease that has a distinct genetic and environmental predilection (Chan, 1998, Quintanilla-Martinez et al, 1999; Lymphoma Study Group of Japanese Pathologists 2000; Au et al, 2005a). Previous studies have suggested a combination of environmental and genetic risk factors for the development ENKTL (Au et al, 2005a;Xu et al, 2007). However, it is not clear whether genetic and/or other factors are also important determinants with regard to the clinical features and outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is considered to be a novel mechanism of malignant cell regulation and has been associated with the development and progression of cancer [13,14]. The role of autophagy in cancer cell death or protection remains unclear [15,16]. Beclin 1, a mammalian ortholog of the yeast Atg6 protein, is an important mediator of autophagy [17][18][19].…”
Section: Introductionmentioning
confidence: 99%